Mandibular adenomatoid odontogenic tumor. About a case. - Alvarez Aguirre, Maria Salome (2020)
Introduction: The adenomatoid odontogenic tumor, is a benign hamartomatous neoplasm of odontogenic type, which constitutes between 3% to 7% of all odontogenic tumors. It occurs in young patients more than females and are located in the upper jaw in the anterior area, mainly the canine, is associated with teeth included, are slow growing, painless and asymptomatic neoplasms. It is classified: follicular, extrafollicular, and peripheral.Case presentation: The case concerns a 22-year-old 8-month-old male patient, with no significant pathological history, who has presented painless bulging in the left paranasal region for 1 year. He goes to dentistry at the Carlos Andrade Marin Hospital, where a panoramic X-ray is performed and an OD 23 (piece 23 that has not erupted) is evidenced, the lesion is related to the orbit, a cystic formation is observed that encompasses the maxilla and maxillary sinus of the left side. Also, the bulge takes up the middle third of the facial region.Discussion: The adenomatoid odontogenic tumor is considered a benign neoplasm that grows progressively and slowly. The treatment of this lesion is enucleation and curettage of the affected area without observing recurrence.